2017
DOI: 10.1097/opx.0000000000001000
|View full text |Cite
|
Sign up to set email alerts
|

The Visual Impact of Lens-Induced Astigmatism is Linked to Habitual Axis

Abstract: The impact of lens-induced astigmatism was dependent on the refractive status of the participants. When investigating the impact of lens-induced astigmatism, it is important to consider the participants' habitual axis of astigmatism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…In general, presbyopes wearing presbyopic corrections appear to adapt to the new visual experiences, to both blur in simultaneous vision images (Radhakrishnan et al, 2014) as well as to distortions and to the presence of asymmetric aberrations produced by progressive lenses (Alvarez, Kim and Granger-Donetti, 2017), in consistency with reported mechanisms of spatial neural adaptation (Sawides et al, 2011) In general, understanding how presbyopic lens designs can be improved, and even customized to the patient's refractive profile, requires understanding focus perception in presbyopic patients and to what extent visual perception with a new correction is affected by prior visual experience. Previous studies have shown adaptation to astigmatism (Marcos et al, 2015;Vinas et al, 2013, Hughes, Mallen andElliott, 2016), reflected by a strong bias in the perception of blur orientation.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…In general, presbyopes wearing presbyopic corrections appear to adapt to the new visual experiences, to both blur in simultaneous vision images (Radhakrishnan et al, 2014) as well as to distortions and to the presence of asymmetric aberrations produced by progressive lenses (Alvarez, Kim and Granger-Donetti, 2017), in consistency with reported mechanisms of spatial neural adaptation (Sawides et al, 2011) In general, understanding how presbyopic lens designs can be improved, and even customized to the patient's refractive profile, requires understanding focus perception in presbyopic patients and to what extent visual perception with a new correction is affected by prior visual experience. Previous studies have shown adaptation to astigmatism (Marcos et al, 2015;Vinas et al, 2013, Hughes, Mallen andElliott, 2016), reflected by a strong bias in the perception of blur orientation.…”
Section: Introductionmentioning
confidence: 93%
“…In addition, young astigmatic subjects appear to be more sensitive to the reduction of visual acuity upon induction of astigmatism than non-astigmats (de Gracia et al, 2011), particularly when astigmatism is induced along the axis of their natural astigmatism (Vinas et al, 2013). Other studies have shown that subjects are not only adapted to their native astigmatism, but also to the magnitude (Sawides et al, 2011) and orientation (Artal, 2004, Sawides et al, 2010b, Hughes, Mallen and Elliott, 2016 of their own aberrations, and that the best perceived focus shifts following adaptation to high order aberrations (Marcos et al, 2015). Achieving optimal best focus is key to providing best optical quality with a correction.…”
Section: Introductionmentioning
confidence: 99%
“…Lens induced astigmatism may affect chartbased visual acuity more than acuity measured with isolated Landolt Cs, because of the potential for the blurred images of adjacent optotypes to interact with each other on charts . It is likely that for isolated letters or for isolated Landolt Cs that doubling will degrade visual acuity less than for our chart‐based measures, because there is no opportunity for adjacent letters to overlap.…”
Section: Discussionmentioning
confidence: 97%
“… 18 A third limitation was the use of optically simulated blur which differs from uncorrected refractive astigmatism, due to magnification effects produced by the defocusing lens and the lack of long-standing neuronal adaptation to the astigmatic error. 54 The sample included in the study did not present significant RA, minimizing the effects of any meridional long-term blur adaptation, 53 , 55 and the effects of blur adaptation on the optical conditions were balanced throughout the sample by randomization.…”
Section: Discussionmentioning
confidence: 99%